2021
DOI: 10.1021/acs.langmuir.1c00548
|View full text |Cite
|
Sign up to set email alerts
|

Probing How Various Metal Ions Interact with the Surface of QDs: Implication of the Interaction Event on the Photophysics of QDs

Abstract: With an aim to understand the mechanism of interaction between quantum dots (QDs) and various metal ions, fluorescence response of less-toxic and water-soluble glutathione-capped Zn−Ag− In−S (GSH@ZAIS) QDs in the presence of different metal ions has been investigated at both ensemble and single-molecule level. Fourier transform infrared (FT-IR) spectroscopy has also been performed to obtain a molecular level understanding of the interaction event. The steady-state data reveal no significant change in QD emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 67 publications
(121 reference statements)
2
18
0
Order By: Relevance
“…The shorter decay component (τ 1 ∼3.8 ns) belongs to the band edge emission; the intermediate (τ 2 ∼38 ns) and longer (τ 3 ∼242 ns) decay components are due to the trap/defect state emission. 59 In presence of BSA, the τ 1 , τ 2 , and τ 3 of ZAIS QD increase to 4.60, 41.11, and 243.6 ns, respectively. Taking into account the relative contribution of lifetime components, a closer look indicates that (τ 1 × b 1 ) increases from 1.01 to 1.10 ns, while (τ 2 × b 2 ) decreases from 11.45 to 11.51 ns, and (τ 3 × b 3 ) increases from 106.48 to 114.49 ns.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…The shorter decay component (τ 1 ∼3.8 ns) belongs to the band edge emission; the intermediate (τ 2 ∼38 ns) and longer (τ 3 ∼242 ns) decay components are due to the trap/defect state emission. 59 In presence of BSA, the τ 1 , τ 2 , and τ 3 of ZAIS QD increase to 4.60, 41.11, and 243.6 ns, respectively. Taking into account the relative contribution of lifetime components, a closer look indicates that (τ 1 × b 1 ) increases from 1.01 to 1.10 ns, while (τ 2 × b 2 ) decreases from 11.45 to 11.51 ns, and (τ 3 × b 3 ) increases from 106.48 to 114.49 ns.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…It can be observed that the fluorescence intensity of QD has been quenched by ∼80% in the presence of NQ, ∼85% in the presence of ANQ, and ∼90% in the presence of HNQ. We note here that depassivation of the surface ligand of QD by naphthoquinones can be ruled out due to the bulky nature of these naphthoquinones. , Moreover, aggregation of QDs in the presence of these analytes cannot also be the cause of fluorescence quenching as no change of emission maxima of QD in the presence of analytes has been observed. , The fluorescence response of all the three analytes has been shown in Figure S7. It is pertinent to take a note here that, upon addition of ANQ/HNQ to QD, no significant increase in the fluorescence intensity of the acceptor units in respective systems also establishes that no appreciable EET process takes place between the QD and the acceptor units that are used in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…The competition mechanism gradually tends to the sulfur source, forming a gradually completed growth process and forming AIS QDs. 48 The interfacial reaction nucleation mechanism of the sulfur source and hydroxide competing cations at the interface of the complex needs certain conditions to be realized. First, there is no high temperature to provide the power for ion nucleation, so the selection of the sulfur source is particularly important.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Under the action of this competitive mechanism, with the continuous consumption of the hydroxide outside the complex in precursor solution, the sulfur source has the opportunity to nucleate and grow with cations. The competition mechanism gradually tends to the sulfur source, forming a gradually completed growth process and forming AIS QDs . The interfacial reaction nucleation mechanism of the sulfur source and hydroxide competing cations at the interface of the complex needs certain conditions to be realized.…”
Section: Results and Discussionmentioning
confidence: 99%